Efficacy and safety results from a phase 1b/2, multicenter, open-label study of oprozomib and dexamethasone in patients with relapsed and/or refractory multiple myeloma. (August 2019) - Hari, Parameswaran; Paba-Prada, Claudia E.; Voorhees, Peter M.; Frye, John; Chang, Yu-Lin; Moreau, Philippe; Zonder, Jeffrey; Boccia, Ralph; Shain, Kenneth H.
Highlights: Efficacy and safety w/ oprozomib-dexamethasone in RRMM patients were investigated. ORR for the 2/7 schedule was 58.7% overall and 46.4% for bor-refractory patients. Limitations including GI toxicities and intrapatient PK variability halted study. New formulation of oprozomib w/ improved gastrointestinal tolerability is warranted. Abstract: Oprozomib is an oral proteasome inhibitor with activity in multiple myeloma (MM). Our phase 1b/2 study examined the safety and efficacy of oprozomib with dexamethasone in patients with relapsed and refractory MM. Oprozomib was administered with a 5/14 or 2/7 schedule with dexamethasone. Phase 1b primary objectives were to determine the maximum tolerated dose (MTD) and recommended phase 2 dose (RP2D) of oprozomib; phase 2 primary objectives were to determine overall response rate (ORR) and safety/tolerability of the RP2D. Between July 2, 2013, and August 29, 2016, data were available on 65 enrolled patients (5/14 schedule, n = 19; 2/7 schedule, n = 46). In phase 1b, MTD was 180 mg (5/14 schedule) and not reached (2/7 schedule); RP2D was 300 mg (2/7 schedule). In phases 1b and 2, ORR across dosing cohorts (210–330 mg) for the 2/7 schedule was 58.7% overall and 46.4% for bortezomib-refractory patients (n = 28). All patients reported ≥1 treatment-emergent adverse event (AE); the most common AEs were gastrointestinal. Grade ≥3 AEs occurred in 78.9% and 82.6% of patients on the 5/14 and 2/7 schedules, respectively. The oprozomib and dexamethasone combination has encouraging activity and could be an important MM therapy if gastrointestinal tolerability is improved.